INSTITUTIONS AND INEQUALITIES - Thomas, Jan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This introductory course will focus on an analysis of social structure and its impact on the experiences of individuals. We will look at the ways in which social structures construct and constrain reality for individuals and how society and social institutions shape individual values, attitudes, and behaviors. The impact of race, class, and gender will be a continuing analytical theme. The course will examine sociological concepts through an analysis of culture, social inequality, social institutions, and social change. The first portion of the class will focus on understanding culture and how we come to be social beings. We will then move to an examination of social stratification and inequalities paying particular attention to the impact of race, class, and gender on the lives of individuals in American society. We will look recent changes in the institutions of economics, politics, and education and the impact these changes have had on individuals and society. We will end the semester by looking at social change as illustrated by changes in American families. By the end of the course, you should understand common sociological concepts and perspectives and be able to consider aspects of the social world through the sociological lens.